Daily field checking list by Walter Rosene, December 24, 1935 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated December 24, 1935. This checklist was used by Walter Rosene to record birds sighted around Boone County with Bob Walker and Walter Jr. between 10:00 and 12:30, and 1:30 and 3:30. Plustek--flatbed